STRUKTUR DAN NILAI BUDAYA MINANGKABAU DALAM NASKAH PASAMBAHAN BATAGAK PANGULU - Rahmadani, Dessy; Juita, Novia; Hamidin, Hamidin (Universitas Negeri Padang, 2013)
The purpose of this article to describe structure and culture value Minangkabau in document Pasambahan Batagak Pangulu. The data of this structure and culture value Minangkabau in document Pasambahan Batagak Pangulu. Analyzed technique do with analysis descriptive and content analysis. The findings of the study is opening obeisance by si pangka and si alek, obeisance statement si pangka and si alek, intention delivery si pangka, obeisance terminate si pangka, confirmation si pangka and si alek, suspension while si pangka and si alek, opening obeisance si alek and si pangka, statement obeisance si alek and si pangka, delivery repeated intention si alek and si pangka, confirmation si alek and si pangka, offering answer and obeisance terminate si alek and si pangka, adaptation si pangka and si alek. Culture value Minangkabau which be contained is humility value and respect for other, agreement value and consensus, fidelity value and accuracy, submissive value and obedient to the custome, the nature of human life, nature of human work, human nature against time, and human nature to nature.